Consumption smoothing and vulnerability in Russia - Gerry, C; Li, C (Taylor and Francis, 2008)
Applying bootstrapped quantile regression to the Russian Longitudinal Monitoring Survey (RLMS) data, we examine the channels through which individuals experience and seek to cope with changes in consumption. We find that married individuals living in small households, with educated heads in urban areas are better equipped to smooth consumption. Investigating the impact of idiosyncratic shocks, we find that the labour market is an important transmission mechanism allowing households to smooth their consumption but also exposing them to risk, mainly through job loss. Outside of pension payments, the formal social safety net does not facilitate consumption smoothing, thus heightening the importance of informal coping institutions. It transpires that both support from relatives/friends and home production act as important insurance mechanisms for the most vulnerable. In contrast with previous findings, it would seem that regardless of its historical, political and social roots, the garden plots and dachas, often romanticized in Russian literature, do provide a means by which ‘urban’ Russians are able to cope with economic fluctuations. We finish by stressing the important policy lessons for Russia's developing market economy.